Teknik Pemeliharaan Induk Ikan Kerapu Batik (Epinephelus Microdon) di UD. Arif Hatchery, Buleleng Bali - Ray Bima Riskila; Anaku Karunia; Anjar Tio Pahlevi; Angger Irawan (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2026)
The camouflage grouper (Epinephelus microdon) is a high-value marine aquaculture species with significant economic importance, making effective broodstock management a key factor in ensuring successful seed production. Healthy and well-managed broodstock play a crucial role in producing high-quality eggs and larvae, thereby improving hatchery productivity. This study aimed to examine the broodstock management practices applied at UD. Arif Hatchery, Buleleng Regency, Bali. A descriptive research design with a direct observation approach was conducted over 60 days through field observations, interviews, and the collection of primary and secondary data. The study involved 15 broodstock maintained in concrete tanks under a flow-through water system with a male-to-female ratio of 3:1. The management practices included tank preparation, broodstock selection, water quality monitoring, feeding with fresh tuna and squid using an at satiation method, disease prevention and treatment, and natural spawning through environmental manipulation to stimulate gonadal maturation. Male broodstock received Hormonviton supplementation to enhance sperm development, while Elbaju was administered to accelerate wound healing in injured fish. No signs of parasitic infection were observed throughout the study, indicating that the broodstock remained healthy under the applied management system. Overall, systematic broodstock management effectively maintained broodstock health, supported reproductive performance, and increased the potential for successful spawning. These findings provide practical guidance for hatchery managers and contribute to improving the efficiency and sustainability of camouflage grouper seed production.